On the nature of the hard X-ray sources SWIFT J1907.3-2050, IGR J12123-5802 and IGR J19552+0044 - Bernardini, Federico (2013)
The INTEGRAL and Swift hard X-ray surveys have identified a large number of new sources, among which many are proposed as Cataclysmic Variables (CVs). Here, we present the first detailed study of three X-ray-selected CVs, Swift J1907.3-2050, IGR J12123-5802 and IGR J19552+0044 based on XMM-Newton, Suzaku, Swift observations and groundbased optical and archival (near-IR) nIR/IR data. Swift J1907.3-2050 is highly variable from hours to months-years at all wavelengths. No coherent X-ray pulses are detected but rather transient features. The X-ray spectrum reveals a multitemperature optically thin plasma absorbed by complex neutral material and a soft blackbody component arising from a small area. These characteristics are remarkably similar to those observed inmagnetic CVs. A suprasolar abundance of nitrogen could arise from nuclear processed material from the donor star. Swift J1907.3-2050 could be a peculiar magnetic CV with the second longest (20.82 h) binary period. IGR J12123-5802 is variable in the X-rays on a time-scale of ≳ 7.6 h. No coherent pulsations are detected, but its spectral characteristics suggest that it could be a magnetic CV of the Intermediate Polar (IP) type. IGR J19552+0044 shows two X-ray periods, ~1.38 h and ~1.69 h and an X-ray spectrum characterized by a multitemperature plasma with little absorption. We derive a low accretion rate, consistent with a CV below the orbital period gap. Its peculiar nIR/IR spectrum suggests a contribution from cyclotron emission. It could either be a pre-polar or an IP with the lowest degree of asynchronism.